Pengukuran Kinerja Keuangan Perbankan Berbasis Analisis Rasio Keuangan - Hayatul Millah; Marmiyantika (Iqtishodiyah : Jurnal Ekonomi dan Bisnis Islam, 2020)
This type of research is quantitative research that has the aim to determine the assessment and development of Islamic financial performance. Measurements were made using a financial ratio analysis approach consisting of liquidity ratios, solvency ratios and profitability. Audited balance sheet and profit and loss data are used as data sources. Based on an analysis of the development of BSM’s financial performance for the period 2013-2017, the ratio of liquidity, solvency and profitability fluctuated. Then the development of financial performance in the BMI 2013-2017 period based on liquidity ratios experienced a significant increase, then based on the solvency ratio showed fluctuations, while based on profitability ratios showed fkultuation. Bank Negara Indonesia Syariah in the period of 2013-2017 experienced fluctuating performance developments when viewed based on its liquidity ratio, based on the solvency ratio showing fluctuations, while based on profitability ratios showed an unstable increase.